A description of the physical properties of selected sediments of the Weichselian and Wartanian glaciations - Labak-Mechowska, Ewa Agnieszka (Bulletin of Geography. Physical Geography Series, 2016)
Subsurface sediments in Poland were deposited mainly in the Pleistocene, and have varying origins and, consequently, differing geological and engineering parameters. Fluvioglacial deposits were formed during both the glacial and interglacial periods, which differed from each other in climatic conditions. Based on the results of laboratory analysis and fieldwork, till and fluvioglacial sands were compared in Central and North-Eastern Poland. The research included consistency limits, relative density, plasticity index, constrained modulus of initial compressibility and modulus of initial deformation. Despite the existing view that there exists a large diversity of geological, engineering and geotechnical parameters of variously-aged deposits in Poland, no major differences in their properties were determined at the study sites.